2007
DOI: 10.1182/blood-2006-04-020024
|View full text |Cite
|
Sign up to set email alerts
|

Proplatelet formation is regulated by the Rho/ROCK pathway

Abstract: Platelets are released by megakaryocytes (MKs) via cytoplasmic extensions called proplatelets, which require profound changes in the microtubule and actin organization. Here, we provide evidence that the Rho/ROCK pathway, a well-known regulator of actin cytoskeleton, acts as a negative regulator of proplatelet formation (PPF). Rho is expressed at a high level during the entire MK differentiation including human CD34 ؉ cells. Thrombopoietin stimulates its activity but at a higher extent in immature than in matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
184
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(209 citation statements)
references
References 42 publications
18
184
1
Order By: Relevance
“…Depending on the experiments, MKs were sorted according to CD41, or CD41 and CD42 expression using Influx flow cytometer (BD, Mountain View, CA) 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the experiments, MKs were sorted according to CD41, or CD41 and CD42 expression using Influx flow cytometer (BD, Mountain View, CA) 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed on CD41 + MK sorted at day 6 of human culture 42 or day 2 of murine culture derived from Lin − liver fetal cells. Cells were examined under the Zeiss LSM.…”
mentioning
confidence: 99%
“…31,32 Recent findings have shown that NMMHC-IIA attenuates proplatelet formation, 33,34 which occurs in terminally mature megakaryocytes where most of the cytoplasm is converted into lengthy beaded extensions. 35 Thus, NMMHC-IIA might restrain thrombopoiesis until megakaryocytes accumulate sufficient quantities of the materials required for optimal platelet assembly; loss of myosin-IIA function could trigger precocious proplatelet formation, whereas gain-of-function mutations might limit platelet production.…”
Section: Discussionmentioning
confidence: 99%
“…In the erythroblast, myosin II could function in an actomyosin contractile apparatus responsible for maintaining a normal cell shape during cell condensation. Rho/ROCK-1 pathway has been shown to be involved in other differentiation systems, including proplatelet formation through MLC2 phosphorylation, 30 and keratinocyte differentiation through stratification and enlargement of cell size. 31 Recent findings also define a cytoskeleton-independent function for ROCK in regulating morphogenesis and cell size Figure 7 ROCK-1 is the main MLC2-regulating kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Retrovirus MIGR-GFP and the retrovirus expressing the dominant-negative form of Rho MIGR RhoA-N19, were produced as described. 30 Erythroid cell infection. CD34 þ cells isolated from cord blood were cultured for 5 days as described then infected by shRNA GIPZ lentiviruses or MIGR-GFP retroviruses.…”
Section: Methodsmentioning
confidence: 99%